INVASION DISEASES OF FISH, THE DEVELOPMENT OF PARASITES - Allamuratova Bibizada Kadirbay kizi (Journal Park Publishing, 2023)
This article presents a comprehensive overview of invasion diseases in fish, focusing on the development of parasites and their ecological impact. It highlights the need for integrated management strategies and emphasizes the significance of early detection and biosecurity measures to safeguard fish populations and aquatic ecosystems. The research draws from various authoritative sources, providing up-to-date and reliable information on the topic.
Keywords: Invasion diseases, fish parasites, fish health, aquatic ecosystem, ecological impact.